(untitled) (Revista de Ciências Agroveterinárias, 2009)
This work was carried out aiming to build and calibrate low cost anemometers to measure the wind speed in the Agrometeorological CAV station. Two Robinsom anemometers with three and four shells and one small anemometer with four shells were built. The construction procedure followed technical approaches regarding to the dimension and operation relationship, employing materials of low cost and the use of manufacture work. The project was performed in the Meteorology and Mechanization section of CAV/ UDESC, in the city of Lages, southern Brazil. A wind tunnel was built according to technical norms of National Association of Fan Manufactures to calibrate the meters. A factory Robinsom anemometer type was also tested. The following relations with the average velocity to the standard meter were obtained: Vp = 1.01 Vm + 2.09 (R2 = 0.96), Vp = 1.09 Vm + 5.32 (R2 = 0.84), Vp = 0.98 Vm + 1.36 (R2=0.92) and Vp = 1.17 Vm + 1.81 (R2=0.95), where Vp is the average speed of the standard meter (km h-1) and Vm is the average speed of the tested anemometer (km h-1), corresponding to the anemometer of four shells, three shells, the small anemometer of four shells and the factory anemometer, respectively.